2022
DOI: 10.3390/antibiotics11081038
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Inhibitor of Enoyl-Acyl Carrier Protein Reductase (InhA) Enzyme in Mycobacterium tuberculosis from Plant-Derived Metabolites: An In Silico Study

Abstract: Mycobacterium tuberculosis (M.tb.) enoyl-acyl carrier protein (ACP) reductase (InhA) is validated as a useful target for tuberculosis therapy and is considered an attractive enzyme to drug discovery. This study aimed to identify the novel inhibitor of the InhA enzyme, a potential target of M.tb. involved in the type II fatty acid biosynthesis pathway that controls mycobacterial cell envelope synthesis. We compiled 80 active compounds from Ruta graveolens and citrus plants belonging to the Rutaceae family for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…From the modeling results, it can be concluded that the potentiation of the 2PD4 and 2GO4 enzymes can lead to an antibacterial effect against gamma-positive and Gram-negative bacteria. The results of molecular docking are in good agreement with the literature data on the study of the potentiation of the enzymatic targets of our choice using antibacterial drugs with new mechanisms of action [ 34 , 35 , 36 ]. Table 3 presents the scoring function (Gibbs energy in kcal/mol) to the corresponding compound end target.…”
Section: Resultssupporting
confidence: 86%
“…From the modeling results, it can be concluded that the potentiation of the 2PD4 and 2GO4 enzymes can lead to an antibacterial effect against gamma-positive and Gram-negative bacteria. The results of molecular docking are in good agreement with the literature data on the study of the potentiation of the enzymatic targets of our choice using antibacterial drugs with new mechanisms of action [ 34 , 35 , 36 ]. Table 3 presents the scoring function (Gibbs energy in kcal/mol) to the corresponding compound end target.…”
Section: Resultssupporting
confidence: 86%
“…Furthermore, Singh et al [ 9 ] compiled a library of 80 compounds from Ruta graveolens and citrus plants belonging to the Rutaceae family for pharmacokinetic and molecular docking analyses. The chemical structures of the 80 phytochemicals and the 3D structure of the mycobacterial target InhA enzyme were obtained from the PubChem database and the RCSB Protein Data Bank, respectively.…”
mentioning
confidence: 99%
“…Until today, both INH and ETH are prodrugs available. They are activated by either KatG or EthA enzyme, respectively, generating a reactive oxygen species (ROS) that ultimately impairs InhA and disrupt mycolic acid chain elongation 13,14 .…”
Section: Fig 1: Enzymatic Pathway Of Mycolic Acid Biosynthesismentioning
confidence: 99%